War and Empire in Mauritius and the Indian Ocean - Jackson, A. author. aut Link
XIV, 241 p.
Keywords: By examining Mauritius and the Indian Ocean, this unique synthesis of imperial and naval/military history, reveals the depths of colonial involvement in the Second World War and the role of colonies in British strategic planning from the eighteenth century. In the century of total war, the British Empire was fully mobilized. The Mauritian home front became regimented, troops were recruited for service overseas, the Eastern fleet guarded the Indian Ocean, and Mauritius became a base for SOE operations and intelligence-gathering for Bletchley.